Knowledge and Practice about Use of Drugs During Pregnancy - G Karwi , Yahya (Diyala Journal of Medicine, 2021)
Background: Drugs used by pregnant women may reach the fetus through the placenta and lead to effects on the development, intellectual ability, birth defects miscarriage and stillbirth. Objective: To assess the knowledge and practice of pregnant women concerning the risk and safety of drug use. Patients and Methods: This cross-sectional study was conducted in a selected sample of Maternal and Child Health (MCH ) clinics and private pharmacies in an Iraqi province for a period of 6 months during 2019. A special questionnaire was designed by the researcher to collect data about the study sample. Results: Out of (250) pregnant included in the current study, 70% of them were between 20-30 year of age. Most of the study population (52%) were of schooling level of education and 70% of them not working. Pregnant whom multigravida was (82%). Of the study population (48%) in their second trimester. Pregnant participants in the current study (56%) were from the out-patient department and (70%) have antenatal care follow -up. Regarding the knowledge of the study population about the risk of the drug (10%) stated that it is risky to the mother, (45%) risky to the baby, (25%) risky to both and about (15% ) stated that drugs are safe during pregnancy. Concerning the study's population’ practice for drug use, the results revealed that (73%) of them use drugs with a medical prescription, (20%) without medical prescription and other use in (7%). Conclusion: The study concluded that the knowledge and practices of pregnant women about taking medicines during pregnancy at an acceptable level and recommends raising awareness about the risks of taking unnecessary medicines for various common diseases during pregnancy.